Chylous ascites following abdominal aortic aneurysmectomy. Management with total parenteral hyperalimentation. - Meinke, A H (1979)
Chylous ascites may follow operative injury to retroperitoneal lymphatics. When possible, early reoperation has been advised. This report describes a patient with chylous ascites following emergency abdominal aortic aneurysmectomy. Because the patient was not a candidate for reoperation, total parenteral hyperalimentation was employed in management. This approach resulted in a successful outcome.